2019
DOI: 10.1007/s00167-019-05461-y
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic osteoarthritis diagnosed within 5 years following ACL reconstruction

Abstract: PurposeThe purpose was to calculate the incidence of osteoarthritis in individuals following Anterior Cruciate Ligament Reconstruction (ACLR) in a large, national database and to examine the risk factors associated with OA development. Methods A commercially available insurance database was queried to identify new diagnoses of knee OA in patients with ACLR. The cumulative incidence of knee OA diagnoses in patients after ACLR was calculated and stratified by time from reconstruction. Odds ratios were calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 43 publications
(53 reference statements)
1
49
1
7
Order By: Relevance
“…However, these predicting methods predict late-stage changes leading to joint replacement, but not the early processes leading to potentially reversible tissue damage. Moreover, successfully predicting PTOA within 2 to 3 years in patients after meniscus repair or partial meniscectomy after ACL tear is somewhat expectable, as advanced joint deterioration is known to be associated with both procedures [237,238]. Despite these facts, the impressive aspect is that they have successfully demonstrated that multi-modality measurements could be used for prediction.…”
Section: Summary Outlook and Early Disease Considerationsmentioning
confidence: 99%
“…However, these predicting methods predict late-stage changes leading to joint replacement, but not the early processes leading to potentially reversible tissue damage. Moreover, successfully predicting PTOA within 2 to 3 years in patients after meniscus repair or partial meniscectomy after ACL tear is somewhat expectable, as advanced joint deterioration is known to be associated with both procedures [237,238]. Despite these facts, the impressive aspect is that they have successfully demonstrated that multi-modality measurements could be used for prediction.…”
Section: Summary Outlook and Early Disease Considerationsmentioning
confidence: 99%
“…We used these criteria for participant age and time since surgery to limit the likelihood that participants would be experiencing symptoms or functional limitations related to OA. 3,16 Volunteers were excluded from the study if they reported a history of lower extremity injury in the 6 weeks before data collection, had any history of lower extremity surgery, or had any chronic medical condition that might have affected their ability to participate in physical activity. Weekly moderate-to-vigorous physical activity and daily step-count data from all healthy participants (n ¼ 42) and most ACLR participants (n ¼ 41) were included in a previous study 7 that assessed differences in physical activity outcomes between individuals with and those without a history of ACLR.…”
Section: Participantsmentioning
confidence: 99%
“…Reinjury rates after primary ACL reconstruction (ACLR) have been reported up to 28% for individuals who to return to high levels of physical activity and sports. 1,2 In addition to high reinjury rates, decreased physical activity, 3 lower subjective function, 4 and early onset posttraumatic osteoarthritis 5,6 have challenged contemporary management strategies for patients rehabilitating after ACLR. To effectively manage healthcare decisions following ACL injury, measures of patient function that best identify patients at risk for secondary ACL injury are needed.…”
Section: Introductionmentioning
confidence: 99%